Let's switch to the cloud - Duso, Tomaso,Schiersch, Alexander (DIW Berlin, German Institute for Economic Research, 2022)
The advent of cloud computing promises to improve the way firms utilize IT solutions. Firms are expected to replace large and inflexible fixed-cost investments in IT with more targeted variable spending in cloud solutions. In addition, cloud usage is expected to increase the productivity of firms, as it allows them to quickly customize the IT they require to their specific needs. We assess these assertions using data on a representative sample of firms provided by the German statistical offices for the years 2014 and 2016, which allows to observe who are the cloud users. Our analysis explicitly accounts for the self-selection into cloud adoption within an endogenous treatment regression framework. Broadband availability at the municipality level is used as an exogenous shifter for cloud usage. We show that, while cloud adoption does not impact IT investment in any sectors, it does significantly improve labor productivity for firms in manufacturing and in information and communication services.
urn:nbn:de:101:1-2022110103415702744135
Keywords: Graue Literatur; cloud computing; investment; productivity; IT; substitution; firm performance